Technical and economic analysis of the project “change from open to pre-assembled networks” applied to an electric power distribution Company. - Laverde Albarracín, Cristian; Guamán Sánchez, Cristian; Carrillo Escobar, Patricio; Herrera Albarracín, Roberto (SATHIRI, 2020)
In Ecuador there are electricity distribution companies that have losses due to theft in the most vulnerable areas of the country, which generates a great problem for companies to counteract these practices; for this reason, Electricity and Renewable Energy Management (MEER) since 2009, implemented a Losses Reduction Plan (PLANREP), which main objective was to neutralize this problem. One of the PLANREP projects implemented in CNEL Santo Domingo Business Unit ( where this study was applied) , it was the change from open to pre-assembled networks, so the objective of this project was to determine the technical and economic efficiency of the project that resulted in the total recovery of non-technical energy losses of the secondary circuits under study; in addition to the economic analysis was determined the rapid recovery of the investment being a profitable project for the distributor.